Thymic stromal lymphopoietin modulates T cell response and improves cardiac repair post-myocardial infarction - Wang, Xuhong; Zheng, Qi; Zha, Lingfeng; Zhang, Lingxue; Huang, Mingkai; Zhang, Si; Zhang, Xuzhe; Li, Qinlin; Chen, Xinglin; Xia, Ni; Zhang, Min; Lv, Bingjie; et al. (Frontiers in Immunology, 2024)
BackgroundThe inflammatory response is associated with cardiac repair and ventricular remodeling after myocardial infarction (MI). The key inflammation regulatory factor thymic stromal lymphopoietin (TSLP) plays a critical role in various diseases. However, its role in cardiac repair after MI remains uncertain. In this study, we elucidated the biological function and mechanism of action of TSLP in cardiac repair and ventricular remodeling following MI.Method and ResultWild-type and TSLP receptor (TSLPR)-knockout (Crlf2-/-) mice underwent MI induction via ligation of the left anterior descending artery. TSLP expression was upregulated in the infarcted heart, with a peak observed on day 7 post-MI. TSLP expression was enriched in the cardiomyocytes of infarcted hearts and the highest expression of TSLPR was observed in dendritic cells. Crlf2-/- mice exhibited reduced survival and worsened cardiac function, increased interstitial fibrosis and cardiomyocyte cross-sectional area, and reduced CD31+ staining, with no change in the proportion of apoptotic cardiomyocytes within the border zone. Mechanistically, reduced Treg cell counts but increased myeloid cell infiltration and an increased ratio of Ly6Chigh/Ly6Clow monocyte were observed in the ani hearts of Crlf2-/- mice. Further, TSLP regulated CD4+ T cell activation and proliferation at baseline and after MI, with a greater impact on Treg cells than on conventional T cells. RNA-seq analysis revealed significant downregulation of genes involved in T cell activation and TCR signaling in the infarcted heart of Crlf2-/- mice compared with their WT counterparts.ConclusionCollectively, our data indicate a critical role for TSLP in facilitating cardiac repair and conferring protection against MI, primarily through regulating CD4+ T cell responses, which may provide a potential novel therapeutic approach for managing heart failure after MI.